The Potential and Approach of Flue Gas Waste Heat Utilization of Natural Gas for Space Heating. (2016) - Zhao, Xiling; Fu, Lin; Yuan, Weixing; Li, Feng; Li, Qingsheng
Abstract: After the combustion of natural gas, the flue gas contains large amounts of water vapor. The latent heat of the water vapor in the flue gas account for 10%-11% of the lower heating value of natural gas, that is, if the condensing heat of the flue gas were recovered, the energy efficiency could be improved greatly. In order to improve the efficiency of the space heating system by natural gas, the potential of waste heat of the flue gas were analyzed, and the problems of the conventional space heating system were proposed. A new approach was proposed, which could decrease the temperature of the flue gas, and recover the waste heat of the flue gas simultaneously. The flue gas outlet temperature could be reduced to below 25 °C. The different processes were proposed for gas boiler, distributed energy system, and natural gas cogeneration systems. The energy saving analysis and economic evaluation were investigated. A remarkable economic advantage can be achieved in this technology. The payback year is within 4 years. It provides the important reference for reasonable application of the technique.